THE AI REVOLUTION IN AD MEASUREMENT: IMPLICATIONS FOR BIG TECH AND ADVERTISERS - Swati Sinha, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative impact of artificial intelligence (AI) on ad measurement in the digital advertising landscape. It examines the shift towards AI-powered solutions driven by the need for greater efficiency and personalization in campaign optimization and analysis. The paper delves into the advanced capabilities of AI algorithms in processing massive datasets, enhancing ad targeting, optimizing bidding strategies, and improving performance tracking. Key benefits of AI-powered ad measurement are discussed, including real-time campaign adjustments, advanced fraud detection, and improved return on investment for advertisers. The article addresses how AI tackles traditional challenges such as cross-device attribution and provides more granular measurement solutions. Through case studies of major tech companies and comparative analyses, the superiority of AI methods over traditional approaches is demonstrated. Ethical considerations and privacy concerns surrounding data collection and AI transparency are critically examined. The paper concludes by exploring future trends in AI ad measurement technology and its potential impact on the advertising industry, highlighting the need for balancing technological advancement with ethical considerations and privacy protection. This comprehensive review provides insights into the current state and future directions of AI in advertising measurement, offering valuable perspectives for marketers, technologists, and researchers in the field.